Recent Advances in Flood Risk Management - Abbot, John; Hammond, Andrew (IntechOpen, 2019)
This book provides a series of topics on flood risk management from around the world. The first section includes models for improved approaches to flood risk management, the importance of groundwater management in the context of floods (focussing on Taiwan), contingency plan for local communities using flood simulation, deciding on response strategies against the identified flood risk before a flood occurs (illustrated for the Philippines) and models for estimating maximum flood heights (illustrated for Mozambique). The second section examines flood risk management relating to the urban environment, with examples from a coastal city in Saudi Arabia and a housing development in Mexico. The third section relates to flood risk management in the context of agriculture, particularly relating to damage to Asian rice crops.